2017
DOI: 10.1080/10400435.2017.1307880
|View full text |Cite
|
Sign up to set email alerts
|

The effect of caster types on global rolling resistance in manual wheelchairs on indoor and outdoor surfaces

Abstract: An important aspect of reducing the strain of wheeling is to decrease rolling resistance. Previous laboratory research, using a treadmill, determined that smaller casters significantly increased rolling resistance. The purpose of this study was to determine the effect of caster size on various indoor and outdoor surfaces on global wheelchair rolling resistance. Three caster types with sizes 4 in, 5 in, and 6 in, three indoor surfaces, and three outdoor surfaces were studied. A manual wheelchair was passively p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…While predicate work has not measured cost of propulsion, studies of overground rolling resistance on carpet found larger diameter casters exhibited lower rolling resistance. 33,34 Since rolling resistance has a direct impact on propulsion cost, this finding would be consistent with an increase in cost. In distinction, during the zero radius turns the 6 00 caster exhibited relatively high cost on both tile and carpet which highlights its caster scrub on these surfaces.…”
Section: Caster Influence On Propulsion Effortmentioning
confidence: 53%
“…While predicate work has not measured cost of propulsion, studies of overground rolling resistance on carpet found larger diameter casters exhibited lower rolling resistance. 33,34 Since rolling resistance has a direct impact on propulsion cost, this finding would be consistent with an increase in cost. In distinction, during the zero radius turns the 6 00 caster exhibited relatively high cost on both tile and carpet which highlights its caster scrub on these surfaces.…”
Section: Caster Influence On Propulsion Effortmentioning
confidence: 53%
“…It was found that a four-inch caster had 16% higher RR than five or six-inch casters and caster shimmy in deceleration tests was found to increase RR. 19 , 33 …”
Section: Resultsmentioning
confidence: 99%
“…It was found that a four-inch caster had 16% higher RR than five or sixinch casters and caster shimmy in deceleration tests was found to increase RR. 19,33 Increased mass. Six articles investigated the total weight of the wheelchair and rider on RR or simply the addition of weight to a test rig (Table 13).…”
Section: Testing Factorsmentioning
confidence: 99%
“…In addition to the evidence on the effect of rear wheel/tire configuration, caster type was also shown to influence wheelchair mobility. The study of Chan et al [ 13 ] showed that caster size is an important factor, with a small caster (4 in) being associated with higher global rolling resistance when compared to 5 in and 6 in casters. Indeed, the study of Zepeda et al [ 14 ] demonstrated a relationship between caster wheel diameters and drag forces in manual wheelchairs, and their findings indicate that the smaller diameters result in a significant increase in the drag forces when the weight distribution is in a way that the user has at least 30% of his/her weight supported by the caster wheels.…”
Section: Introductionmentioning
confidence: 99%